Andrew Jackson papers - Jackson, Andrew, 1767-1845.
Correspondence, military papers, and other papers reflecting most phases of Jackson's military and political career. Subjects include his law practice in Tennessee, his service in the U.S. Congress; Florida and Tennessee state politics; the War of 1812; Creek War, 1813-1814; Battle of New Orleans, 1815; Indian affairs; Eaton Affair (Petticoat Affair) involving John Henry Eaton and his wife, Peggy Eaton; Nullification Crisis, 1828-1832; national economic policy; Bank of the United States; and the Panic of 1837. Correspondents include Francis Preston Blair, Willie Blount, John C. Calhoun, R.K. Call, William C.C. Claiborne, John Coffee, Alexander James Dallas, Andrew Jackson Donelson, John Henry Eaton, John Forsyth, Edmund Pendleton Gaines, Felix Grundy, Robert Young Hayne, Amos Kendall, Henry Lee, William Berkeley Lewis, James Monroe, James Kirke Paulding, Franklin Pierce, James K. Polk, John Randolph, John C. Rives, John Sevier, Roger Brooke Taney, and Levi Woodbury.
Microfilm edition available (series 1-9 and 11)
Microfilm produced from originals in the Manuscript Division.
U.S. president, senator, representative, and army officer from Tennessee.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index published by the Library of Congress in 1967 available in the Library of Congress Manuscript Reading Room. Cataloged in record 67060014.
Keywords: Blair, Francis Preston, -- 1791-1876 -- Correspondence; Blount, Willie, -- 1768-1835 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Call, R. K. -- 1791-1862 -- Correspondence; Claiborne, William C. C. -- 1775-1817 -- Correspondence; Coffee, John, -- 1772-1833 -- Correspondence; Dallas, Alexander James, -- 1759-1817 -- Correspondence; Donelson, Andrew Jackson, -- 1799-1871 -- Correspondence; Eaton, John Henry, -- 1790-1856.; Eaton, John Henry, -- 1790-1856 -- Correspondence; Eaton, Peggy, -- 1799?-1879.; Forsyth, John, -- 1780-1841 -- Correspondence; Gaines, Edmund Pendleton, -- 1777-1849 -- Correspondence; Grundy, Felix, -- 1777-1840 -- Correspondence; Hayne, Robert Young, -- 1791-1839 -- Correspondence; Jackson, Andrew, -- 1767-1845 -- Friends and associates; Kendall, Amos, -- 1789-1869 -- Correspondence; Lee, Henry, -- 1756-1818 -- Correspondence; Lewis, William Berkeley, -- 1784-1866 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Paulding, James Kirke, -- 1778-1860 -- Correspondence; Pierce, Franklin, -- 1804-1869 -- Correspondence; Polk, James K. -- 1795-1849 -- Correspondence; Randolph, John, -- 1773-1833 -- Correspondence; Rives, John C. -- 1795-1864 -- Correspondence; Sevier, John, -- 1745-1815 -- Correspondence; Taney, Roger Brooke, -- 1777-1864 -- Correspondence; Woodbury, Levi, -- 1789-1851 -- Correspondence; Bank of the United States (1816-1836); Creek War, 1813-1814.; Depressions -- 1836-1837.; Indians of North America -- Government relations; New Orleans, Battle of, New Orleans, La., 1815.; Nullification (States' rights); Practice of law -- Tennessee; Florida -- Politics and government -- 1821-1865.; Louisiana -- History -- War of 1812.; Tennessee -- Politics and government -- To 1865.; United States -- Economic conditions -- To 1865.; United States -- Economic policy -- To 1933.; United States -- History -- War of 1812.; United States -- Politics and government -- 1829-1837.; United States -- Politics and government -- 1783-1865.; Army officers; Presidents -- United States; Representatives, U.S. Congress -- Tennessee; Senators, U.S. Congress -- Tennessee